The plethora, clinical manifestations and treatment options of autoimmunity in patients with primary immunodeficiency - (:unkn) unknown (TURKISH PEDIATRICS ASSOC, 2016)
Aim: Although the association between primary immunodeficiency and autoimmunity is already well-known, it has once again become a topic of debate with the discovery of newly-defined immunodeficiencies. Thus, investigation of the mechanisms of development of autoimmunity in primary immunodefficiency and new target-specific therapeutic options has come to the fore. In this study, we aimed to examine the clinical findings of autoimmunity, autoimmunity varieties, and treatment responses in patients who were genetically diagnosed as having primary immunodeficiency. Material and Methods: The files of patients with primary immunodeficiency who had clinical findings of autoimmunity, who were diagnosed genetically, and followed up in our clinic were investigated. The demographic and clinical features of the patients and their medical treatments were evaluated. Results: Findings of autoimmunity were found in 30 patients whose genetic mutations were identified. The mean age at the time of the first symptoms was 8.96 +/- 14.64 months, and the mean age of receiving a genetic diagnosis was 82.55 +/- 84.71 months. The most common diseases showing findings of autoimmunity included immune dysregulation, polyendocrinopathy, enteropathy X-linked syndrome (16.7%); autoimmune lymphoproliferative syndrome (10%); lipopolysaccharide-responsive beige-like anchor protein deficiency (10%); and DiGeorge syndrome (10%). Twelve (40%) patients showed findings of autoimmunity at the time of first presentation. The most common findings of autoimmunity included inflammatory bowel disease, inflammatory bowel disease-like findings (n=14, 46.7%), immune thrombocytopenic purpura (n=11, 36.7%), and autoimmune hemolytic anemia (n=9, 30.0%). A response to immunosupressive agents was observed in 15 (50%) patients. Ten patients underwent hematopoietic stem cell transplantation. Six patients were lost to follow-up due to a variety of complications. Conclusion: Autoimmunity is frequently observed in patients with primary immunodeficiency. The possibility of primary immunodeficiency should be considered in patients with early-onset manifestations of autoimmunity, and these patients should be carefully monitored in terms of immunodeficiency development. Early diagnosis of primary immunodeficiency may provide favorable outcomes in terms of survival.
Keywords: Autoimmunity; autoimmune hemolytic anemia; inflammatory bowel disease; primary immunodeficiency; PRIMARY IMMUNE-DEFICIENCY; X-LINKED SYNDROME; CUTANEOUS GRANULOMAS; T-CELLS; POLYENDOCRINOPATHY; DYSREGULATION; ENTEROPATHY; DISEASE; DISORDERS; MUTATIONS